Tryptophan metabolite-regulated Treg responses contribute to attenuation of airway inflammation during specific immunotherapy in a mouse asthma model. Issue 8 (2nd August 2020) - Hu, Qi; Jin, Ling; Zeng, Jing; Wang, Jinyu; Zhong, Shimin; Fan, Wenting; Liao, Wei
ABSTRACT: In allergen-specific immunotherapy for asthma, antigens attached to dendritic cells increase the tryptophan metabolism in these cells and alter the Th17/Treg balance in the airways. Tryptophan metabolism has long been suggested to be relevant in the pathophysiology of allergic disorders, including asthma. Our study investigated whether tryptophan metabolites are responsible for the changes in Th17/Treg balance and decreases in airway hyperreactivity and inflammation seen during allergen-specific immunotherapy in an asthma model. Ovalbumin was injected intraperitoneally into mice to establish an asthma model, and then high dose ovalbumin allergen-specific immunotherapy was administered to induce immune tolerance. Airway hyperreactivity and serum ovalbumin-specific immunoglobulin E were measured to assess whether the animal model was successfully established. We then examined the influence of inhibition of tryptophan metabolism and the addition of tryptophan metabolites on allergen-specific immunotherapy-induced changes in the Th17/Treg balance and decreases in airway inflammation and inflammatory cytokines. Production of tryptophan metabolites was partly responsible for the allergen-specific immunotherapy-induced increase in Tregs, decrease in airway inflammation, and decrease in inflammatory cytokines. Ovalbumin-specific immunoglobulin E and airway hyperreactivity were not affected. In the context of asthma, an increase in tryptophan metabolites is one of the mechanisms by which allergen-specific immunotherapy achieves immune tolerance.